IOT based water leakage monitoring system / Muhammad Azfar Shazmi Mohd Adnan and Zulkifli Mohamed - Mohd Adnan, Muhammad Azfar Shazmi; Mohamed, Zulkifli (2021)
Nowadays, water leakage has become one of the major issues in the water distribution system and it can cause a lot of water loss through water pipelines. Hence, it will give a financial loss if it cannot be identified at an early stage. The concept of real-time water leakage monitoring using the Internet of Things is presented in this project. The internet of things (IoT) is a key component of smart tracking, which uses wireless sensor technologies to link people and systems. The parameter used to analyse the water leakage in the pipeline is the water flow sensor. In this study, a water flow sensor is used to determine the rate of water flow via a pipeline in order to resolve any water-related concerns such as leakage and usage. The proposed system would concentrate on common housing pipes and would display collected data through a smartphone. Additionally, this project will build the case for the water flow sensor, as well as the full circuitry for all electronics needed. As a result, it shows that the system can function stably and give water flow rate readings with 98% accuracy. The system can also send real-time data to smartphones via the Blynk application and alert the users when leaks are identified using threshold data.